Modulation of Human Melatonin MT1 Receptor By Valproic Acid and its Effects in Combination with Melatonin on Human Breast Cancer - Jawed, Sana (My University, 2007)
The MT1 receptor is involved in the oncostatic action of melatonin and valproic acid (VPA) in human MCF-7 breast cancer cells and VPA can upregulate this receptor in C6 glioma cells. Therefore, the effect of VPA on the expression of the MT1 was examined in MCF-7 cells. Treatment of MCF-7 cells in low serum conditions with VPA (0.5 or 1mM) for 24 or 72 h caused a significant increase in MT1 receptor expression, as shown by reverse transcription-polymerase chain reaction analysis (RT-PCR). MTT [3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assays performed in high serum conditions revealed a significant concentration-dependent inhibition of MCF-7 cell proliferation by VPA (0.5 - 5 mM), whereas melatonin (1 or 10 nM) showed modest effects alone. However, a combination of VPA and melatonin produced a marked synergistic inhibition of cell proliferation. In subsequent experiments, under high serum conditions, VPA treatment for 24h on these cells resulted in a significant decline of MT1 mRNA while the protein levels were still increasing, as seen by RT-PCR and western blotting respectively. The involvement of multiple biochemical events, such as: induction of the p53 tumor suppressor gene and repression of the estrogen receptor (ER)-alpha might be responsible for the synergistic inhibition of these cells after the simultaneous exposure to VPA and melatonin. These results indicate that clinically relevant concentrations of VPA upregulate melatonin MT1 receptor expression in human breast cancer cells. Moreover, the enhanced antiproliferative effect observed with a combination of VPA and melatonin suggests that a similar therapeutic approach may be beneficial in human breast cancer.
Keywords: modulation, human melatonin MT1 receptor, valproic acid, human breast cancer, oncostatic, gene